Pengaruh kinerja keuangan pada nilai perusahaan dengan pengungkapan corporate social responsibility sebagai variabel pemoderasi - Purwaningsih, Ni Kadek Irma; Wirajaya, I Gde Ary (E-Jurnal Akuntansi; Vol 7 No 3 (2014), 2014)
The purpose of this study was to examine the effect of financial performance using variable Return on Assets in corporate value using Tobin's Q variable using a moderating variable that disclosure of corporate social responsibily, there are 21 manufacturing companies that were sampled with observation number 63. Purposive sampling is a sampling technique in this study. Test MRA (Moderated Regression Analysis) is an analysis of the data used in this study.Statistically, the results of this study show that financial performance has a positive and significant effect on firm value. Corporate Social Responsibility is not statistically significant effect on the value of the company, and Corporate Social Responsibility Disclosure statistically not able to moderate influence on the value of the company's financial performance. Keywords : Return on Assets, Tobin's Q , Corporate Social Responsibility .
Keywords: Return on Assets; Tobin' s Q; Corporate Social Responsibility.